2013
DOI: 10.1111/emre.12013
|View full text |Cite
|
Sign up to set email alerts
|

Management Innovation in Focus: The Role of Knowledge Exchange, Organizational Size, and IT System Development and Utilization

Abstract: This study aims to examine the correlates of management innovation at the organizational level. We propose that internal knowledge exchange acts as a crucial predictor of management innovation. To fine-tune the link between knowledge exchange and management innovation, we examine the mediating explanatory mechanism of IT system development and utilization, as well as the moderating boundary role of organizational size. In an attempt to find generalizable patterns across cultures, we test the model using mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 63 publications
0
31
0
1
Order By: Relevance
“…Results indicated that the model fit the data well. Given the relevance of providing more than one index (e.g., Černe et al ., ), we calculated NFI (Normed Fit Index = 0.967), CFI (Comparative Fit Index = 0.976), IFI (Incremental Fit Index = 0.976) and TLI (Tucker Lewis Index/Non‐Normed Fit Index = 0.971). Further, the RMSEA score and the Standardized RMR, both equal to 0.049, also showed a satisfactory fit (Hu and Bentler, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results indicated that the model fit the data well. Given the relevance of providing more than one index (e.g., Černe et al ., ), we calculated NFI (Normed Fit Index = 0.967), CFI (Comparative Fit Index = 0.976), IFI (Incremental Fit Index = 0.976) and TLI (Tucker Lewis Index/Non‐Normed Fit Index = 0.971). Further, the RMSEA score and the Standardized RMR, both equal to 0.049, also showed a satisfactory fit (Hu and Bentler, ).…”
Section: Methodsmentioning
confidence: 99%
“…A long tradition supports the notion that knowledge sharing is a critical determinant for organizations' success (Černe et al ., ). Given that strategic knowledge often concentrates in certain units and individuals, by sharing their ideas and knowhow employees can hasten the development of new products, strengthen mutual learning, and contribute to their own creativity (Mesmer‐Magnus and DeChurch, ).…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, it was only until recently that one could find literature about management innovation that is related to transitional and developing economies (García-Zamora et al 2013;Wu et al 2008), especially studies from the region of South-East Europe, with the exception of a few studies from Slovenia (Černe et al 2013;Ursič & Mulej, 2005). Consequently, each study on this topic significantly contributes to the body of literature on management innovation.…”
Section: Q2: Is the Existing Theory And Practice Of Management Innovamentioning
confidence: 99%
“…Mol & Birkinshaw 2009b;Walker et al 2011;Černe et al 2013). Authors of these studies strove to reveal the causes and/or effects of the management innovation process at an organizational level, and they identified a lack of such research work as a major gap in the existing literature This study built on these previous research and sought to further reduce the identified gap in the literature.…”
mentioning
confidence: 99%
“…In order to support the knowledge integration, much of the research into the management issues concerning the role of information technologies has been focusing on the knowledge management system (KMS) (Černe et al, 2013;Sutanto and Jiang, 2013;Wang et al, 2014).…”
Section: Contemporary Research Themesmentioning
confidence: 99%